Determinants of Performance and Constraints faced by Farmer Producer Organizations (FPOs) in India - Kumar, Sanjiv; Kumar, Ranjit; Meena, P C; Kumar, Alok (Indian Journal of Extension Education, 2023)
Farmer Producer Organization (FPO) is believed to improve the livelihood of farmers by collectivizing them for input purchase and providing forward linkage. In order to understand the determinants of performance and the constraints faced by them, the study was undertaken by surveying 125 FPOs of Andhra Pradesh, Madhya Pradesh, Telangana, Maharashtra and Uttar Pradesh during April-August 2022. It was found that most of the FPOs are engaged in input supply followed by produce aggregation. The FPOs with more number of enterprising activities were able to achieve higher turnover and better net profit. Multiple regression was used to identify the determinants of paid-up capital and turnover of FPO. Members number, BOD size and years of existence were found to be the determinants of paid-up capital of FPO. Paid-up capital was found to be significant predictor of turnover of FPO. Capital requirement was found to be the biggest constraint facedby FPO in achieving better performance. It was concluded that for increasing the turnover, the FPO should focus on increasing the paid-up capital as paid-up capital can be used for scaling up and expanding the business. Extending capital loan as well as working capital loan to FPO should be made easy.